Western Union Telegram - Western Union:::Creator::::::::::::
Photograph of a Western Union Telegram to JS from Melanchony Blacky. Sent [1939 05 21]. It reads: '4 F SV 70 NL Reno Nevada [1939 05 21] John Steinbeck Steinbeck Ranch Alma California Knowing you are live one we Reno dings want you consider lvg M Campbell of Golden Hotel put on you cant use a blind ding anyhow he's too good for us if you give go by over forty hours twenty of us will hop coal eight ann cop a heel at your ranch until you turn man again what he asks is nickel to what we needs are relief Melanchony Blacky [06:28]' Handwritten note on the side reads: 'Phoned [1939-05-22 09:00] 293R.1'